Smoking habits and awareness of smoking risks depending on academic background in university students - Saleiro,Sandra (2008)
Objective: To evaluate smoking habits among a group of medical students and engineering students in order to assess whether, depending on their specific academic background, differences in smoking habits and attitudes towards smoking were present. Methods: Medical and engineering students from the Oporto University were surveyed using a questionnaire, in which they were asked to mention their smoking habits, their perception about cigarette dependence and to point out, from a list of 12 tobacco-related diseases, which were associated with tobacco use. Results: A total of 338 students (172 of Medicine and 166 of Engineering) with median age of 21 years answered the questionnaire. Prevalence of smoking was 21.6% and was greater among males than females (31.8% versus 10.9%). Significantly fewer medical students smoked (16.3%), compared to engineering students (27.1%). Almost 16% of the students did not know nicotine ability to induce dependence, but medical students were more aware of it (p=0.00). All students identified lung cancer as being associated with tobacco use and pointed out, less frequently, other diseases. Except for lung cancer, medical students showed a better knowledge about smoking-related diseases. Conclusions: As expected, medical students showed a better knowledge of smoking-related diseases in general, as compared to engineering students, and they also showed a lower prevalence of smoking habits. This difference may be due to different attitudes towards smoking for which different academic backgrounds may have contributed.